A Predictive Model for Parametrial Invasion in Patients With FIGO Stage IB Cervical Cancer: Individualized Approach for Primary Treatment. Issue 1 (January 2016) - Kong, Tae-Wook; Piao, Xianling; Chang, Suk-Joon; Paek, Jiheum; Lee, Yonghee; Lee, Eun Ju; Ryu, Hee-Sug
Abstract : Objective: The aim of this study was to preoperatively identify high- and low-risk subgroups of patients with parametrial involvement in those with FIGO (International Federation of Gynecology and Obstetrics) stage IB cervical cancer treated with radical hysterectomy according to menopause. Materials and Methods: We retrospectively reviewed data of 197 patients with FIGO stage IB cervical cancer. None of the patients had definite evidence of parametrial invasion in a preoperative examination and underwent type III radical hysterectomy between February 2006 and March 2015. Preoperative risk criteria predicting parametrial involvement were identified in premenopausal and postmenopausal women, respectively. Results: Tumor size on magnetic resonance imaging (MRI) more than 4 cm (odds ratio [OR], 10.029; 95% confidence interval [95% CI], 2.300–43.741; P = 0.002) and serum squamous cell carcinoma–antigen level of 3.60 ng/mL or more (OR, 4.132; 95% CI, 1.086–5.723; P = 0.037) were independent factors for parametrial invasion in premenopausal women. Significant factors associated with parametrial involvement in postmenopausal women were tumor size on MRI more than 3 cm (OR, 11.353; 95% CI, 2.614–49.306; P = 0.001) and Cyfra 21-1 level of 2.40 ng/mL or more (OR, 8.048; 95% CI, 1.240–52.221; P = 0.029). Patients were categorized into low- and high-risk groups according to risk criteria. Significant differences in the rates of parametrial invasion were observed between the groups (2.3% vs 38.6% in the premenopausal group, P < 0.001; 11.1% vs 77.3% in the postmenopausal group, P < 0.001). Conclusions: A model using preoperative tumor size on MRI, serum squamous cell carcinoma–antigen, and Cyfra 21-1 level was highly predictive of parametrial invasion in patients with FIGO stage IB cervical cancer. In particular, postmenopausal women were likely to have microscopic parametrial invasion, even among tumors 3 cm or less. Therefore, individualized approaches considering several preoperative factors are needed.